2014
DOI: 10.1128/jcm.00453-14
|View full text |Cite
|
Sign up to set email alerts
|

PCR-Based Detection and Molecular Characterization of Shiga Toxin-Producing Escherichia coli Strains in a Routine Microbiology Laboratory over 16 years

Abstract: dShiga toxin-producing Escherichia coli (STEC) is a heterogeneous group of bacteria causing disease ranging from asymptomatic carriage and mild infection to hemolytic uremic syndrome (HUS). Here, we describe patients with STEC infection and characterize the STEC strains detected in our laboratory by use of PCR for stx 1 , stx 2 , and eae from 1996 through 2011. Patient information was collected from referral forms and from the Norwegian Surveillance System for Communicable Diseases. STEC isolates were characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 46 publications
3
17
0
Order By: Relevance
“…Our data support that HUS development is dependent on ageassociated factors as shown in previous studies (25). Our findings correlate with those of a recent study showing that the age of the patient (Ͻ5 years) and the presence of eae and stx 2a genes in STEC showed significant associations with the development of HUS (P Ͻ 0.05 for each parameter), while stx 1 -positive STEC was associated with non-HUS cases (P Ͻ 0.05) (24). Nonetheless, age is not the sole determining factor for disease progression, and additional investigation is needed to identify the genetic determinants of HUS.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Our data support that HUS development is dependent on ageassociated factors as shown in previous studies (25). Our findings correlate with those of a recent study showing that the age of the patient (Ͻ5 years) and the presence of eae and stx 2a genes in STEC showed significant associations with the development of HUS (P Ͻ 0.05 for each parameter), while stx 1 -positive STEC was associated with non-HUS cases (P Ͻ 0.05) (24). Nonetheless, age is not the sole determining factor for disease progression, and additional investigation is needed to identify the genetic determinants of HUS.…”
supporting
confidence: 92%
“…Strains belonging to seropathotype A contained almost all of the virulence genes tested (stx 2 , espY1, espY3, eae-gamma, nleD-2, espX2, espO1-1, lpfA, espY4-2, espX6, and etpD). The presence of genes espK, eae, espG, terE, ureD, espV, espN, espX7, ecs1763, ecs1822, espM1, nleF, nleG, nleH1-2, espJ, espM2, espW, efa1, efa2, ent, nleB, and nleE can be used to differentiate strains belonging to seropathotypes B from those belonging to seropathotypes D and E. These data corroborate a recent study showing that these potential virulence genes were significantly more frequent among HUSassociated than non-HUS-associated strains (24). Interestingly, five clinical non-O157 isolates lacking the eae gene were associated with human disease; four isolates also lacked stx 2 and three lacked most of the virulence genes tested.…”
supporting
confidence: 88%
“…Furthermore, VF that play an important role in toxin production and attachment to host cells were highly associated with PT groups I ϩ II or PT group I alone, while other VF were associated with PT group III. Previous studies also reported that the number of VF present in STEC isolates increases the pathogenic potential of STEC and the strong association of certain accessory VF with severe illness and outbreaks (12,17,22,27,33,34,36,44). Interestingly, the accessory virulence gene content of the stx 2f -positive STEC isolates that clustered in a distinct branch with two stx-negative EPEC isolates was lower than the other STEC isolates categorized in PT group II.…”
Section: Discussionmentioning
confidence: 85%
“…While the stx subtypes stx2a and stx2c and the LEEpositive strains are associated with a high risk of more serious illness (9,(22)(23)(24), other virulence gene combinations (even in E. coli strains that lack the stx genes) may also be associated with severe disease, including HC and HUS (12,(25)(26)(27). Furthermore, patient characteristics and infectious doses also determine the outcome of disease (28).…”
mentioning
confidence: 99%
“…Characterize STEC detected by use of PCR for detection of stx1, stx2 and eae genes from 996 through 2011. STEC isolates were characterized with respect to serogroup or serotype, (Haugum et al, 2014).…”
Section: Discussionmentioning
confidence: 99%